Doctoral scientists and engineers in the United States : 1995 profile - Brown, Prudence; Henderson, Peter (NSF (Series), 1998)
Presents "Doctoral Scientists and Engineers in the United States: 1995 Profile," a report from the U.S. National Science Foundation Division of Science Resources Studies. Notes that the report is available in HTML and PDF formats.